THE EFFECT OF INFLATION LEVEL AND GOLD PRICES ON THE DISTRIBUTION OF RAHN'S FINANCING IN PT. PEGADAIAN (PERSERO) SHARIA BRANCH ALAMAN BOLAK PADANGSIMPUAN - berlin berlin; abdul nasser hasibuan; sarmiana batubara; idris saleh (Institut Agama Islam Negeri Padangsidimpuan, 2021)
This research is motivated by the financing of rahn distributed by PT. Pegadaian (Persero) Syariah Branch of Alaman Bolak Padangsidimpuan from 2015-2018 has always experienced an increase. In 2015 rahn financing disbursed amounted to Rp. 12,722,736 experienced an increase in 2016 by 10% to Rp. 14,171,000, then continued to increase in 2017 by 11% to Rp. 15,877,390 while in 2018 it increased by 1% in the amount of Rp. 15,918,480, but the level of inflation and the price of gold Padangsidimpuan City has increased and decreased. This is very possible because the inflation rate is very influential to the rising cost of gold and the price of gold can be said to affect the distribution of financing because some people who mortgaged their goods in the form of gold to obtain funds. This research is quantitative research. Data sources used are primary data and secondary data. To collect the required data is done by using the interview and documentation method, namely the 2015-2018 monthly financial statements PT. Pegadaian (Persero) Syariah Branch of Alaman Bolak Padangsidimpuan, with a total sample of 48 months. Data were processed with the help of SPSS program version 23. Based on statistical test results partially the inflation rate does not affect the distribution of rahn financing, this can be proven in the hypothesis testing results of the inflation rate variable having tcount (-1,639) ttable (-1,679), then H0 is accepted Ha is rejected, and the gold price variable has t (2,353) ttable (1,679), then H0 is rejected Ha is accepted, then the inflation rate and gold price variables simultaneously influence the distribution of rahn financing with the results of Fcount (4,435) Ftable (3,204) means that H0 is rejected and Ha is accepted, from the determination test obtained the calculation of 18.4% is determined by the inflation rate and the price of gold and the remaining 81.6% is explained by other variables.